China's renewable energy law and policy: A critical review. (January 2019) - Liu, Junxia
Abstract: Renewable energy, as an important part of the world's energy system, is conducive to the harmonious development of humanity and nature. China has been paying considerable attention to renewable energy given the growing pressure of energy shortages and environmental deterioration. The legal framework of renewable energy in China has greatly contributed to the achievements already made in this field; however, it is still insufficient to integrate renewable energy into the national energy system. This paper, in light of the comparisons of various state practices, critically reviews the problems of China's renewable energy law and policy such as problems with fragmentation, obsolescence, and lack of operability. In addition to identifying the consequent disadvantages, this review also presents improvement recommendations. Highlights: The world is facing serious problems of energy shortage, environmental pollution and climate change. China has established a relatively complete renewable energy law and policy system to promote renewable energy development. Smooth development of renewable energy is inseparable from supportive legal framework. Compared with other states, China's renewable energy laws and policies have some disadvantages to be improved.